Deposit behaviour in Indonesia Islamic banking : do crisis and fatwa matter? - Abduh, Muhamad; Sukmana, Raditya (2011)
This paper attempts to examine factors that influence deposit behaviour of bank depositors in Indonesia Islamic banking. Several explanatory variables are tested namely interest rate, Islamic deposit rate, inflation, income as well as financial crisis. Cointegration test and impulse response functions are utilized to examine the long run and short run relationship among the variables. The period of analysis is from December 2000 to January 2011 (122 number of observation-monthly data). The results show that crisis has no significant impact on the volatility of Islamic banks deposits. This suggests that the Islamic banks’ expansion towards the real economic activities by partnership contracts is one of the best practices. It depicts also that depositors have a strong believe towards the resilience of Islamic banks against financial crisis and thus, they did not withdraw their money excessively during the crisis. However, it is also found that interest rate and income are still dominating the people’s decision to deposit their funds in Islamic banks which in turns, indicating the effectiveness of the anti-riba campaign in Indonesia is still low and thus, the strategy of educating the people need to be redesigned.